(untitled) (Journal of Engineering, 2013)
Roller compacted concrete (RCC) is a concrete of no slump, no reinforcement, no finishing, and compacted using vibratory roller. When compared with conventional concrete, it contains less water content when compared to traditional concrete. The RCC technique achieves significant time and cost savings during the construction of concrete. This study demonstrates the preparation of RCC slab of (38 ×38× 10) cm samples by using roller compactor which is manufactured in local markets. The Hydrated lime additive is used to study the mechanical and physical properties of that RCC slab samples. This investigation is divided into two main stages: The First stage consists of hammer compaction method with two gradation of aggregate, dense and gap graded aggregate, using five percentages of cement content (10, 12, 14, 16, and 18) as a percentage of the total aggregate content. This stage is carried out for selecting the maximum dry density, optimum moisture content, and optimum cement content which is utilized in RCC slab samples construction, a total of 49 cylinder samples sized (10 cm diameter and 11.6 cm high) are prepared. The Second stage is classified into two sub stages; the first one consists of constructing RCC slab samples using roller compaction, 12% cement as a percentage of total aggregate weight has been used according to the data obtained from first stage, this group presents reference mixes without additives. While the second sub stage presents RCC mix with hydrated lime additive and with the same gradation of mixes compact by hammer compaction method, hydrated lime was implemented as (5, 10, 12, and 15) percentage as a partial replacement of cement content. Both of physical and mechanical properties of RCC are studied using cores, sawed cubes, and sawed beams obtained from RCC slab samples. The properties studied were porosity, absorption, and compressive strength, splitting tensile strength and flexural strength by using third point loading method. The results show that hydrated lime improved the overall properties of RCC as compared to reference mix. Mixes with 5% lime give the optimum values for most of strength properties. Dense graded mixes with hydrated lime show superior properties as compared to gap graded mixes.